Continuous real-time breath analysis in ruminants: effect of eructation on exhaled VOC profiles. (14th May 2018) - Oertel, Peter; Küntzel, Anne; Reinhold, Petra; Köhler, Heike; Schubert, Jochen K; Kolb, Johann; Miekisch, Wolfram
Abstract: Background . The analysis of volatile organic compounds (VOCs) in breath allows non-invasive investigations of diseases. Animal studies are conducted as a model to perform research of VOCs and their relation to diseases. In large animal models ruminants were often used as experimental targets. The effect of their physiological eructation on VOC exhalation has not been examined yet and is the objective of this study. Methods . Continuous breath profiles of two young cattle, four adult goats and four adult sheep were measured through a mask, covering mouth and nose, in real-time (200 ms) by means of proton transfer reaction time of flight mass spectrometry. Each animal was analysed twelve times for 3 consecutive minutes. Results . Real-time monitoring yielded a distinction of different episodes in the breath profiles of ruminants. An algorithm to separate eructation episodes and alveolar breath was established. In the first exhalation after eructation at least 19 VOC concentrations increased (up to 36-fold) and went back to initial levels in subsequent exhalations in all investigated ruminants. Decay of concentrations was substance specific. In goats, less VOCs were affected by the eructation compared to cattle and sheep. Breath profiles without exclusion of eructation episodes showed higher variations and median values than profiles where eructation episodes were excluded. Conclusion. Real-time breath analysis of ruminants enables the discrimination and characterisation of alveolar breath and eructation episodes. This leads to a better understanding of variation in breath data and possible origins of VOCs: breath or digestion related. To avoid impairment of breath gas results and to gain further information on bacterial products from the rumen, eructation and alveolar breath data should be analysed separately.